Pemenuhan Hak Keadilan dalam Perkara Pidana Anak melalui Penerapan Asas Diversi di Pengadilan Negeri Pekanbaru Riau - Murofikoh, Dede Ika; Nasihi, Ahmad Ali Abdun (AHKAM, 2022)
Children who are the golden generation often face legal problems. The state exists to protect children in the face of legal problems, in this case known as the principle of diversion. The research method that the author uses in this study is descriptive analytical, which presents an appropriate picture of the characteristics and nature of the problem situation in the study to be then analyzed and processed in accordance with the practice of applying positive law supported by law. theories that correlate with the problem in general.